EFFECT OF TRAINING AND DEVELOPMENT ON EMPLOYEE PERFORMANCE AT THE BUNGOMA COUNTY REFERRAL HOSPITAL, KENYA - Everlyne Naumwo Efumbi,; Dr. Anthony O. Alexis, (IJRDO - Journal of Applied Management Science, 2020)
The health sector in Kenya is ranked as one of the major basic needs and as one of the pillars of vision 2030 as well as the constitution, high priority is placed on the provision of health services and service delivery. The determinations of priorities in public hospitals systems include resource allocations, expenditure and human resource in areas of training and development, involvement, performance appraisal and compensation. The main objective of this study was to analyze the effect of human resource management practices on employee performance in Bungoma County Referral Hospital. The study set out to determine the effect of training and development on employees performance at Bungoma County Referral Hospital. The target population for the study was 99 respondents. Self-administered Questionnaires designed on a 5-point Likert scales range from strongly disagree to strongly agree were used to collect data from the employees working in different departments of the hospital. Questionnaires were distributed among the 99 targeted respondents to get the data required for conducting the analysis. Random sampling technique was used as sample selection method. Data analysis was done using descriptive statistics, namely percentages and frequencies. The study found out that the hospital has training policy programme to staffs, the hospital has a staff development programme in place, the hospital organizes seminars and workshops for its employees, the hospital has a budget for training every year while there is no assessment for training done before choosing employees to be trained and most staffs were uncertain about if the training employees improves their work performance. The study further established that hospitals allow employees to participate in key decision making. The solid foundation of any successful hospital is its staffs. Employees represent a source of knowledge and ideas, but oftentimes that resource remains untapped. Involving employees in the decision-making process not only empowers them to contribute to the success of an organization, but also saves the company time and money in increased productivity and reduced outsourcing. Hospital employees are consulted by management before making decisions on issues touching them and employee attitude surveys are carried out annually. Employees are involved in decision making and Suggestion boxes are placed in a central place for use by employees to contribute ideas for improvement. The study too found out that the hospital has a competitive reward and compensation system; Incentives given to employees motivate and enhance their performance.